WhatsApp use in a health education group with women - Ellen Letícia da Silva Ribeiro; Ana Maria Nunes da Silva; Priscilla Shirley Siniak dos Anjos Modes; Sonia Silva Marcon; Jeane Cristina Anschau Xavier de Oliveira; Áurea Christina de Paula Corrêa; Maira Liliane dos Santos Pereira (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To analyze the use of Information and Communication Technologies and the interaction in a health education group with women on WhatsApp. Methodology: Descriptive-exploratory, qualitative research with mothers assisted in two Basic Health Units in Sinop - MT, part of a University Extension Project that used three health education strategies ("G-Day", "Health Tips", and "Educational Video") and project team members. Data were collected between October and December 2021 from messages in the WhatsApp group and submitted to Thematic Content Analysis. Results: Two categories were identified, showing the information provided by the team and specific information requested by the mothers; the doubts expressed by the mothers mobilized the communication-interaction among the participants and little to no interaction was provoked by the health information contained in the educational strategies used. Final consideration: WhatsApp proved to be an important resource/strategy in communication-interaction for health education with women.